Management of asynchronous multifocal adult glioblastoma with loss of BRAFV600E -mutant clonality: a case report - Hannah Haile; Pavan S. Upadhyayula; Esma Karlovich; Michael B. Sisti; Brian J. A. Gill; Laura E. Donovan (Acta Neuropathologica Communications, 2025)
Abstract Glioblastoma (GBM) classification involves a combination of histological and molecular signatures including IDH1/2 mutation, TERT promoter mutation, and EGFR amplification. Non-canonical mutations such as BRAFV600E, found in 1–2% of GBMs, activate the MEK-ERK signaling pathway. This mutation can be targeted by small molecule inhibitors, offering therapeutic potential for GBM. In this case report, we describe the management of a 67-year-old male with BRAFV600E -mutant GBM, who experienced both local clonal and distant non-clonal BRAFV600E -mutant recurrences. Initial treatment involved surgical resection followed by radiotherapy and temozolomide (TMZ). Subsequent recurrences were managed with re-resection and dabrafenib/trametinib combination therapy. Notably, a new, non-clonal BRAFV600E -negative tumor developed in a distant location, highlighting the challenge of clonal evolution and resistance in GBM management. The patient’s disease ultimately progressed despite multiple lines of therapy, including targeted inhibition. Identifying mechanisms of resistance and tailoring flexible treatment approaches are essential for advancing outcomes in BRAFV600E -mutant GBM. This case emphasizes the value of molecular profiling in personalizing treatment for patients with multifocal disease. The evolving nature of these tumors requires persistent clinical monitoring and treatment adjustments based on tissue diagnostics.